Let it be: mindful acceptance down-regulates pain and negative emotion. Issue 11 (27th January 2020) - Kober, Hedy; Buhle, Jason; Weber, Jochen; Ochsner, Kevin N; Wager, Tor D
Abstract: Mindfulness training ameliorates clinical and self-report measures of depression and chronic pain, but its use as an emotion regulation strategy—in individuals who do not meditate—remains understudied. As such, whether it (i) down-regulates early affective brain processes or (ii) depends on cognitive control systems remains unclear. We exposed meditation-naïve participants to two kinds of stimuli: negative vs. neutral images and painful vs. warm temperatures. On alternating blocks, we asked participants to either react naturally or exercise mindful acceptance. Emotion regulation using mindful acceptance was associated with reductions in reported pain and negative affect, reduced amygdala responses to negative images and reduced heat-evoked responses in medial and lateral pain systems. Critically, mindful acceptance significantly reduced activity in a distributed, a priori neurologic signature that is sensitive and specific to experimentally induced pain. In addition, these changes occurred in the absence of detectable increases in prefrontal control systems. The findings support the idea that momentary mindful acceptance regulates emotional intensity by changing initial appraisals of the affective significance of stimuli, which has consequences for clinical treatment of pain and emotion.